Single-step Synthesis of Activated Carbon from Arabica Spent Coffee Ground using K2CO3 as Activator Agent - Mieldan, Ghina Ivana; Yuliusman, Yuliusman (Journal of Materials Exploration and Findings, 2024)
Activated carbon is a nanomaterial that is often used as an effective adsorbent. Activated carbon raw materials can use biomass, such as coffee grounds, which can be found along with the growth of public interest in coffee drinks. Chemical activators are used for activation to increase biomass carbon's adsorption capacity. Using K2CO3 activator to increase the specific surface area of activated carbon is more harmless than KOH. The use of spent coffee grounds as carbon source and food additive K2CO3 as an activator can make food-grade activated carbon that can be used for food. This study aimed to synthesize activated carbon in one-step synthesis by utilizing coffee grounds biomass waste by varying the mass ratio between biomass waste and K2CO3. The activated carbon was characterized using SEM- EDX and iodine numbers. Activated carbon was prepared with spent coffee ground and K2CO3 with the mass ratio of 1:1 gained the largest surface area of 1052 m2.g-1 despite having the lowest yield of 18%.